Chapter Trust and security in Italy - Golia, Silvia (Proceedings e report, 2023)
Starting from 2018, the European University Institute's European Governance and Politics Programme developed an international survey in order to monitor the development of Solidarity in Europe. The text of the survey changed across the four available waves, but there were sections remained unchanged over the years, that is the ones concerning security (how secure or insecure do you feel about each of the following areas?) and trust in national government and European Union (how much do you trust ... to make things better in the following area?). The interesting thing in these three sections is that they are composed of the same 10 areas (items) on a 4 point Likert scale. The data are not longitudinal, given that the subjects changes at each time span, so the four waves can be considered together, and Differential Item Functioning (DIF) across time can be used as a tool to investigate, for each area, if and how the difficulty to feel secure or to trust significantly changes over time. This use of DIF analysis if far from its common use, which is connected with the assessment of the validity of a scale, given that it tests the invariance of an item with respect to the characteristics of the subjects (a typical example is the gender). The focus is on Italy. Moreover, applying the Rating Scale Model (RSM), which is a model belonging to the Rasch family of models, it is possible to study the evolution of the perceived security and owned trust, analysing the distance between the estimated mean of each latent trait and the mean item difficulty, which was set to zero. It is not possible to compare directly the different distributions over the years because the measures obtained from the RSM are on the logit scale, which is an interval scale.